LA PROPIEDAD DE LOS DERECHOS DE EMISIÓN DE LOS EVENTOS DEPORTIVOS Y SU REPERCUSIÓN EN LOS INFORMATIVOS: EL CASO DE ANTENA 3, LA 1 Y TELECINCO - Rubén GALLARDO PARRÓN,Manuel MONTES VOZMEDIANO (Fonseca, Journal of Communication, 2023)
This research has been concerned with the treatment given in the sports section of your information leading national TV channels hearing to consider whether prioritize information dew sporting events whose allowances have. There is also an interest in knowing about that sports are reported and confirm whether there is a difference between public television news and news of the private channels. It has been confirmed that there are clear differences in the coverage of sporting events offered by broadcasters, depending on whether the channel has ownership of the allowances of the event. It was also found that La 1 ofree more sports news in their news and is not limited to reporting on sports events that ratings hoard.